My guide smart cane for the visually impaired person integrated with GPS tracker, voice & vibration alerts, and 3-way sensors / Aklil Ebadi Harun ... [et al.] - Harun, Aklil Ebadi; Fadlinazich, Farel Endy; Maulana, Rizqy; Biyyananda, Ilham Rahmadi; Zubairi, Muhammad Saif; Arafa, Ahmad Mujtaba (2022)
Blind individuals encounter difficulties related to the utilization of canes, notwithstanding the indispensable role played by these devices in facilitating orientation and mobility. Canes serve as practical implements that empower autonomous ambulation, even in light of the swift progress witnessed in technology and alternative assistive solutions. Thus, an innovative design of a cane, integrated with better technology is proposed in this study, namely My Guide to help the visually impaired with mobility. My Guide features a box-shaped design with various components which includes multiple sensors, a charging port, a small speaker, three potentiometer caps for adjusting sensor distance, and a water sensor to detect stagnant water, facilitating user mobility. Additionally, My Guide incorporates a GPS Tracker, enabling the user's close contacts to track their location. Furthermore, it is equipped with a voice recorder to enhance user monitoring in each environment. Through extensive sensor testing, all sensors performed well. Coupled with its affordable price, My Guide stick holds significant market potential, catering to a wide range of users.